LEAF ANATOMICAL ADAPTATIONS OF FOURTEEN TREE SPECIES GROWING IN LAGOS STATE UNIVERSITY, OJO CAMPUS. LAGOS, NIGERIA - Omolokun, Kehinde Theophilus; Oluwa, Omoteso K.; Sharaibi, Olubunmi J.; Keshinro, Olajide M.; Mamudu, Mustapha M.; Vincent, Temisan O.; Oloyede, Olanrewaju J.; Jayeola, Adeniyi A. (FUDMA JOURNAL OF SCIENCES, 2024)
Plants growing in different locations exhibit various anatomical adaptations which make them survive in their various habitats. Therefore, this study examined the leaf anatomical adaptations  of fourteen tree species namely Acacia auriculiformis, Albizia lebbeck, Anacardium occidentale, Azadirachta indica, Carica papaya, Delonix regia, Gmelina arborea, Lagestroemia speciosa, Mangifera indica, Polyalthia longifolia, Tectona grandis, Terminalia catappa, Terminalia ivoriensis and Yucca gigantea growing in Lagos State University, Ojo Campus.. The leaf epidermal layers were isolated using nail polish; and were observed under the light microscope to determine the stomata features, epidermal cell and trichome types. The results showed that all the species were hypostomatic, with the exception of Acacia auriculiformis and Terminalia ivorensis that were amphistomatic. Eight stomatal complex types such as anomotetracytic, staurocytic, anisosytic, brachyparacytic, paracytic, pericytic, brachyparatetracytic and anomocytic were observed among the species. The stomatal density ranged from 46.05 mm-2 342.11 mm-2 on both leaf surfaces. The stomatal index ranged from 16.17% - 91.23% on both leaf surfaces. Trichomes were found in Albizia lebbeck, Delonix regia, Gmelina arborea, Polyalthia longifolia, Tectona grandis and Terminali aivorensis. The anticlinal cell wall patterns observed were round, curved, wavy and straight; while the epidermal cell shapes were irregular, isodiametric and polygonal. This study revealed that leaf anatomical adaptations such as amphistomatic leaf type, presence of stomatal complex types (anomocytic, anomotetracytic, brachyparatetracytic, staurocytic and anisocytic) with many subsidiary cells; high stomatal density and index; absence of trichomes; and wavy anticlinal cell wall pattern might be responsible for survival of the species in their locations.